General and Practical Formation of Thiocyanates from Thiols. Issue 6 (17th December 2014) - Frei, Reto; Courant, Thibaut; Wodrich, Matthew D.; Waser, Jerome
Abstract A new method for the cyanation of thiols and disulfides using cyanobenziodoxol(on)e hypervalent iodine reagents is described. Both aliphatic and aromatic thiocyanates can be accessed in good yields in a few minutes at room temperature starting from a broad range of thiols with high chemioselectivity. The complete conversion of disulfides to thiocyanates was also possible. Preliminary computational studies indicated a low energy concerted transition state for the cyanation of the thiolate anion or radical. The developed thiocyanate synthesis has broad potential for various applications in synthetic chemistry, chemical biology and materials science.